(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2007)
We describe and illustrate a partial skull and mandible of a large sabertooth cat from Sahabi, Libya, and refer it to Amphimachairodus aff. A. kabir. A review shows the Miocene Machairodontinae from Africa to be a heterogeneous assemblage, with both small and large forms spanning the entire Late Miocene. The Sahabi form belongs to the group of larger sized taxa, along with A. kabir from Chad and some previously undescribed specimens from the Wembere-Manonga Formation, Tanzania. Both the Sahabi and Chad specimens have relatively slender lower carnassials, similarly to Homotherium, though derived features of the skull and mandible suggest that they are not in the direct ancestry of that genus.